Enamel thickness trends in Plio-Pleistocene hominin mandibular molars. Issue 85 (August 2015) - Skinner, Matthew M.; Alemseged, Zeresenay; Gaunitz, Charleen; Hublin, Jean-Jacques
Abstract: Enamel thickness continues to be an important morphological character in hominin systematics and is frequently invoked in dietary reconstructions of Plio-Pleistocene hominin taxa. However, to date, the majority of published data on molar enamel thickness of Pliocene and early Pleistocene hominins derive from naturally fractured random surfaces of a small number of specimens. In this study we systematically analyze enamel thickness in a large sample of Plio-Pleistocene fossil hominins ( n  = 99), extant hominoids ( n  = 57), and modern humans ( n  = 30). Based on analysis of 2D mesial planes of section derived from microtomography, we examine both average and relative enamel thickness, and the distribution of enamel across buccal, occlusal, and lingual components of mandibular molars. Our results confirm the trend of increasing enamel thickness during the Pliocene that culminates in the thick enamel of the robust Australopithecus species, and then decreases from early Homo to recent modern humans. All hominin taxa share a regional average enamel thickness pattern of thick occlusal enamel and greater buccal than lingual enamel thickness. Pan is unique in exhibiting the thinnest average enamel thickness in the occlusal basin. Statistical analysis indicates that among Pliocene hominins enamel thickness is a weak taxonomic discriminator. The data underlying these results are included in a table in the Supplementary Online Material.